Tocotrienol Rich Fraction Reverses Age‐Related Deficits in Spatial Learning and Memory in Aged Rats. Issue 9 (12th July 2014) - Taridi, Nursiati Mohamad; Abd Rani, Nazirah; Abd Latiff, Azian; Wan Ngah, Wan Zurinah; Mazlan, Musalmah
Abstract: Little is known about the effect of vitamin E on brain function. Therefore, in this study we evaluated the effect of tocotrienol rich fraction (TRF) on behavioral impairment and oxidative stress in aged rats. Thirty‐six male Wistar rats (young: 3‐months‐old; aged: 21‐months‐old) were treated with either the control (olive oil) or TRF (200 mg/kg) for 3 months. Behavioral studies were performed using the open field test and Morris water maze (MWM) task. Blood was taken for assessment of DNA damage, plasma malondialdehyde (MDA) and vitamin E, and erythrocyte antioxidant enzyme activity. Brains were also collected to measure vitamin E levels. Results showed that aged rats exhibited reduced exploratory activity, enhanced anxiety and decreased spatial learning and memory compared with young rats. DNA damage and plasma MDA were increased, and vitamin E levels in plasma and brain were reduced in aged rats. Aged rats supplemented with TRF showed a markedly reduced level of anxiety, improved spatial learning and memory, reduced amount and severity of DNA damage, a reduced level of MDA, and increased levels of antioxidant enzyme activity and plasma/brain vitamin E compared with age‐matched controls. In conclusion, TRF supplementation reverses spatial learning and memory decline and decreases oxidative stress in aged rats.